Unexpected hair regrowth in a woman with longstanding Alopecia universalis - Akritidou, Fani; Misiou, Konstantina; Tsanidou, Elina; Katsaras, Georgios N.; Papamitsou, Theodora (GMS Ophthalmology Cases, 2021)
Alopecia areata (AA) is an autoimmune disorder leading to non-scarring hair loss. As long as hair follicles are not destroyed, the potential for hair regrowth remains. Alopecia universalis is a severe form of AA and the chance of full hair regrowth is below 10%. We present a case of a 55-year-old woman with longstanding AA, who presented to the Outpnt Clinic of our Hospital Unit with almost full eyelashes and hair regrowth after an emotional stressful event. She reported no hair regrowth for the last 35 years. There are few case reports which have exhibited that hair follicles are still alive and may be reactivated after many years.